2009
DOI: 10.1007/s10552-009-9432-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequently cited sources in cancer news coverage: a content analysis examining the relationship between cancer news content and source citation

Abstract: The media are a frequent and sometimes sole source of cancer information for many people. News coverage of cancer can be influential to cancer-related practices such as prevention or detection behaviors, and sources cited by journalists may be influential in shaping this coverage. A content analysis (n = 3,656 stories) revealed that the most frequently cited sources in cancer news articles-research institutions and medical journals-receive disproportionately more attention compared to the National Cancer Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Providing information through media sources can improve knowledge and alter attitudes and health behaviours (Brown et al 2001, Gollust and Lantz 2009, Slater et al 2009, Moriarty et al 2010. The possible adverse effects of poor infant nutrition practices deserve to be fully and consistently explained to caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Providing information through media sources can improve knowledge and alter attitudes and health behaviours (Brown et al 2001, Gollust and Lantz 2009, Slater et al 2009, Moriarty et al 2010. The possible adverse effects of poor infant nutrition practices deserve to be fully and consistently explained to caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…This study acknowledges that examining the source cited is somewhat limited in nature in that it is not known how much influence the uncited source affects the content of the story (Moriarty, Jensen, & Stryker, 2010). There might be situations where the journalists use the sources but did not cite the source intentionally or unintentionally.…”
Section: Limitation and Future Researchmentioning
confidence: 97%
“…Researchers who can provide in depth knowledge base about event and its associated matters as source of information cited were underutilized in this study. Previous research found that research information was an influential source of information cited in the case of breast cancer news coverage (Moriarty, Jensen, & Stryker, 2010), library and information science (Blessinger & Hrycaj, 2010). In sport specific, Lee, Kim, and Love (2014) found that the most common sources of information cited for the Gay Games, a global mega sporting event, is lesbian, gay, bisexual, and transgender (LGBT) community followed by supporters, sport writers, and politicians.…”
Section: Jpes ®mentioning
confidence: 99%
“…[8] The study shows that journal articles are an important source of information for the popular media that report science news.…”
Section: Review Of Literaturementioning
confidence: 99%